Investigating the Causal Relationship Between Achievement Motivation and Academic Optimism with Grit, Mediated by Self-Regulation - Parsai Moghadam, Marzieh; Khanjani, Mehdi; Borjali, Ahmad (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The present study aimed to examine the structural relationships between achievement motivation and academic optimism with grit, considering the mediating role of academic self-regulation among university students.Methods and Materials: This study employed a descriptive correlational design using structural equation modeling (SEM). The statistical population consisted of undergraduate students enrolled during the 2019–2020 academic year at Shahid Chamran University of Ahvaz, from which 230 participants were selected through convenience sampling. Data were collected using four standardized instruments: the Achievement Motivation Questionnaire (Hermans), the Academic Optimism Scale (Tschannen-Moran et al.), the Academic Self-Regulated Learning Strategies Questionnaire (Zimmerman & Martinez-Pons), and the Grit Scale (Duckworth et al.). The validity of the instruments was assessed through confirmatory factor analysis, and reliability was confirmed using Cronbach’s alpha coefficients. Data analysis was conducted using SPSS version 24 and AMOS version 24, and the bootstrap method was applied to test indirect effects.Findings: The results of SEM indicated that achievement motivation had a significant direct effect on academic self-regulation and grit. Academic self-regulation also had a significant direct effect on grit. Academic optimism showed a significant direct effect on grit but did not have a significant direct effect on academic self-regulation. Furthermore, achievement motivation had a significant indirect effect on grit through academic self-regulation, confirming the mediating role of self-regulation. However, the indirect effect of academic optimism on grit through academic self-regulation was not statistically significant. Overall, the final model demonstrated an acceptable fit to the data based on standard fit indices.Conclusion: The findings highlight the central role of achievement motivation in enhancing both self-regulated learning and grit, as well as the importance of self-regulation as a key mechanism linking motivation to perseverance.